THE MODERN ARCHITECTURAL SOLUTIONS FOR UNIVERSITY BUILDINGS (Innovative Technologica: Methodical Research Journal, 2021)
The article discusses the development of modern forms of higher education institutions, compact layout of educational buildings and methods of designing the location of industrial buildings on the territory of the university.